Analysis on the Diversified Payment in the Marketing Service of Power Supply Company - Ling, Zhi (Journal of Theory and Practice of Social Science, 2023)
The recovery efficiency of electric charge is related to the capital operation and recovery efficiency of enterprises. It is the main profit channel of power supply companies, and the recovery rate of electric charge of power supply companies is an important index to measure their management efficiency and profitability. With the rapid development of science and technology, payment methods gradually become diversified. The advantages and disadvantages of various payment methods play different roles in avoiding the risk of electricity charge recovery. In order to give full play to the role of diversified payment methods, this paper briefly describes the diversified payment methods in the marketing service of power supply companies, and analyzes the significance and effect of diversified payment methods in the marketing service of power supply companies.